Pengaruh Jumlah Wisatawan dan Jumlah Hotel terhadap Pertumbuhan Ekonomi Provinsi Lampung - Nuris Sanida; Dwi Rahayu (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
This study aimed to analyze the effect of the number of tourists and the number of hotels on economic growth in Lampung Province during the period 2019–2024. This study employed a quantitative approach using secondary data obtained from the Central Bureau of Statistics (BPS). The data used were panel data consisting of time series and cross-section data, allowing a more comprehensive analysis of regional economic growth dynamics. The analysis method used in this study was panel data regression with the assistance of EViews 13 software. Model selection was conducted through several tests, namely the Chow test, Hausman test, and Lagrange Multiplier test to determine the most appropriate estimation model. The results showed that the number of tourists had a positive and significant effect on economic growth in Lampung Province, indicating that an increase in tourist visits stimulated economic activities through various supporting sectors such as transportation, trade, and services. In contrast, the number of hotels did not have a significant effect on economic growth. However, the simultaneous test showed that the number of tourists and the number of hotels jointly had a significant effect on regional economic growth. These findings indicated that the tourism sector played an important role in supporting regional economic growth, particularly through increasing tourist visits. Therefore, improving tourist destinations, supporting infrastructure, and tourism promotion was necessary to encourage sustainable economic growth in Lampung Province.